Highly transparent MgAl0.5Ga1.5O4 ceramic for overcoming the trade-off between infrared transmittance and mechanical properties. (15th July 2022) - Tu, Bingtian; Tu, Guangsheng; Wang, Hao; Yang, Zhangfu; Wang, Weimin; Fu, Zhengyi
Abstract: A spinel-type MgAl0.5 Ga1.5 O4 transparent ceramic was prepared by pressureless sintering with hot isostatic pressing (HIP) post-treatment. The fully dense transparent ceramic with an average grain size of 47.5 μm exhibits excellent mechanical properties and wide transmission range. The transmission wavelength covers a range of 0.23–7.4 μm. The in-line transmittance is above 84.3% in the 3–5 μm atmospheric window. The thermal conductivity is 11.46 W·m −1 ·K −1 at ambient temperature. Benefiting from the introduction of stronger Al–O bonds in the crystal lattice, the hardness, Young's modulus, and shear modulus of ceramic material were enhanced to 12.2, 269.8, and 105.1 GPa, respectively. The superior overall performance of the MgAl0.5 Ga1.5 O4 transparent ceramic offers a chance to overcome the trade-off between infrared transmittance and mechanical properties. Graphical abstract: Image, graphical abstract .